PO 18067 - Application of 5% lidocaine patch to painful surgical scars: clinical trial - da Rocha Macedo, Rafael; Gonçalves dos Santos, João Paulo; Mendes Júnior, João; Smith Lobato, Emanuel; Putini, Dario; Miller Reis Rodrigues, Luciano; Yukio Ikemoto, Roberto (Scientific Journal of the Foot & Ankle, 2019)
Introduction: Chronic postoperative pain, defined as persistent pain at the surgical incision site 3 months after a procedure, is a common complaint in orthopedic practice. Almost 50% of patients who undergo orthopedic surgery are presumably affected by this complaint. The objective of this study is to evaluate the lidocaine patch 5% as a method for neuropathic pain treatment after orthopedic surgery compared with therapeutic massage performed over the incisions. Methods: This is a prospective, randomized clinical trial of 37 patients who underwent orthopedic surgery from January 2015 to February 2017. All individuals were assessed using the pain visual analog scale (VAS) and the 36-Item Short Form Survey (SF-36) quality of life questionnaire at treatment onset and at 30, 60 and 90 days of treatment. Results: Both groups showed improvement in pain, although the group using the patch showed a greater reduction of pain over time. There were no significant differences in the parameters assessed by the SF-36: physical functioning, physical role functioning, vitality, emotional role functioning, social role functioning, general health perceptions or mental health. The main advantage of the patch lay in the degree of patient satisfaction, which was significantly higher than that of massage, most likely because the patch is easily applied and generates a psychological effect as a drug therapy. Conclusion: The lidocaine patch and massage are effective treatment methods for reducing scar pain that show similar results. The patch is associated with an improvement in the degree of patient satisfaction.